Genetic and ultrasonographic analyses of fetuses with 1q21.1q21.2 microdeletion/microduplication: a retrospective study - Nan Guo; Huili Xue; Bin Liang; Hailong Huang; Meiying Cai; Liangpu Xu (BMC, 2023)
Abstract Background 1q21.1q21.2 microdeletions/microduplications are rare and incompletely penetrant genetic mutations, and only a few reports regarding their prenatal diagnosis are currently available. Here, we analyzed the ultrasonographic phenotypic characteristics of fetuses with these mutations to improve the understanding, diagnosis, and screening of these mutations during gestation. Methods We retrospectively analyzed 8700 cases of pregnant women who underwent invasive prenatal screening by karyotyping and chromosomal microarray analysis (CMA) between November 2016 and November 2021. Results CMA revealed copy number changes in the 1q21.1q21.2 region of eleven fetuses, of which five had microdeletions and six had microduplications. These eleven fetuses exhibited variable ultrasonographic phenotypes. Of the five fetuses with the microdeletion, one exhibited a right-dominant heart, permanent right umbilical vein, and mild tricuspid regurgitation, another showed thickened nuchal translucency, and the remaining three had normal ultrasound phenotypes. Two of the six cases with 1q21.1q21.2 microduplication had structural malformations; one of them had a bilateral subependymal cyst, neck mass, and enlarged cardiothoracic ratio, while the other had right ventricular hypoplasia. Of the remaining four cases, two exhibited nasal bone dysplasia, one showed measurement slower than that during menopause and mild tricuspid regurgitation, and another did not show any notable abnormality in ultrasound examination. Among the eleven cases of 1q21.1q21.2 microdeletion/microduplication, only the parents of two fetuses underwent pedigree verification. The parents of these two fetuses with 1q21.1q21.2 microdeletion syndrome chose to continue the pregnancy, and all aspects of postnatal follow-up were normal. The parents of the other nine fetuses refused pedigree verification; of these cases, four cases terminated, and five cases continued the pregnancies. The five continued pregnancies were followed up after birth; no abnormalities were found. Conclusions Fetuses with 1q21.1q21.2 microdeletion/microduplication show different ultrasound characteristics and may have congenital heart disease, thickened nuchal translucency, and nasal bone dysplasia or show no notable abnormalities in an ultrasound examination. Our study highlights that CMA as a powerful diagnostic tool for these diseases can provide an accurate genetic diagnosis, while improving prenatal diagnosis standards.